The Anxiety of the Pandemic: Binge-watching, Splurging, Sexting, Hooking Up, and Masturbating among College Students. Issue 11 (2nd November 2022) - Mowen, Thomas J.; Heitkamp, Amanda
ABSTRACT: The global coronavirus (COVID-19) pandemic has significantly altered the lives of college students across the United States. Following the outbreak of COVID-19 in the spring of 2020, college campuses were shuttered, classes moved to remote instruction, and university activities, celebrations, and events were canceled. Cast against a backdrop of uncertainty about the future, studies have documented that the pandemic has significantly increased anxiety among college students as they adjust to a "new normal." Drawing from general strain theory, we examine the influence of specific COVID-19-related strains on a variety of changes in student behavior including binge-watching streaming services, splurging on online shipping, sexting, "hooking up" with random people, and masturbating. Results using structural equation models on data from 1, 287 students at a Midwestern university show that specific sources of strain directly are related to binge-watching, online shopping, hooking up with random people, and masturbating, while anxiety was directly related to increased binge-watching, online shopping, and sexting. Anxiety mediated the pathways between some sources of strain and binge-watching and splurging on online shopping. Overall, findings highlight that the global pandemic not only induces anxiety and interrupts academic life but also carries far-reaching consequences for a wide range of behaviors.